THE SAFAVID DYNASTY AND THE ROLE OF SHAH ABBAS I IN THE DEVELOPMENT OF SEVERAL FIELD - Meirison Meirison; Husnul Fatarib; Desmadi Saharuddin (UIN Imam Bonjol Padang, 2021)
The legitimization of the Shah was managed through his bloodline - as in those who were Sayyid or descendants of Prophet Muhammad were automatically considered legitimate rulers of the state. The highest position in the government was the position of Grand Vizier (Prime Minister), who was the closest man to the Shah and had absolute power over national interests. Any decision had to be made after the approval of Shah and the Vizier himself. With the historical method, starting from heuristic data collection and interpreting it, which ends with historiography, Safavid fought the Ottomans, his enemies to the West, who saw the Safavid Empire as a threat Sunni-Shia divide. Many Shiites were deported from the Ottoman Empire following the numerous uprisings in favor of the Safavids. He fought them and lost territories such as Baghdad, parts of the Iranian Azerbaijan region, Herat, Mashhad, etc. However, after his defeats and loss to the Ottomans, he lost the support he enjoyed from the Qizilbash, which had a significant influence in the Empire - but their impact was reduced during the reign of Shah Abbas I. He managed to retrieve the lost territories and increase the number of people serving the military to defend the borders. Was Shah Abbas I. Abbas also managed to fight the Uzbeks and Ottomans and retrieve the lost territories, which positively impacted his reputation and increased power? He managed to recover Herat (modern-day Afghanistan) and Mashhad (Iran) from the Uzbeks, Baghdad, Caucasian territories, and eastern parts of Iraq from the Ottomans.Keywords:Development, Safavid, Shah Abbas I,